Microbiology, ecology, and application of the nitrite-dependent anaerobic methane oxidation process - Shen, Li-Dong; Hu, Bao-lan (Frontiers in Microbiology, 2012)
Nitrite-dependent anaerobic methane oxidation (n-damo), which couples the anaerobic oxidation of methane to denitrification, is a recently discovered process mediated by “Candidatus Methylomirabilis oxyfera.” M. oxyfera is affiliated with the “NC10” phylum, a phylum having no members in pure culture. Based on the isotopic labeling experiments, it is hypothesized that M. oxyfera has an unusual intra-aerobic pathway for the production of oxygen via the dismutation of nitric oxide into dinitrogen gas and oxygen. In addition, the bacterial species has a unique ultrastructure that is distinct from that of other previously described microorganisms. M. oxyfera-like sequences have been recovered from different natural habitats, suggesting that the n-damo process potentially contributes to global carbon and nitrogen cycles. The n-damo process is a process that can reduce the greenhouse effect, as methane is more effective in heat-trapping than carbon dioxide. The n-damo process, which uses methane instead of organic matter to drive denitrification, is also an economical nitrogen removal process because methane is a relatively inexpensive electron donor. This mini-review summarizes the peculiar microbiology of M. oxyfera and discusses the potential ecological importance and engineering application of the n-damo process.